Information Retrieval Technology 10th Asia Information Retrieval Societies Conference, AIRS 2014, Kuching, Malaysia, December 3-5, 2014. Proceedings - Jaafar, Azizah; Mohamad Ali, Nazlena; Azman Mohd Noah, Shahrul; Smeaton, Alan F.; Bruza, Peter; Abu Bakar, Zainab; Jamil, Nursuriati; Mohd Tengku Sembok, Tengku; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 10th Information Retrieval Societies Conference, AIRS 2014, held in Kuching, Malaysia, in December 2014. The 42 full papers were carefully reviewed and selected from 110 submissions. Seven tracks were the focus of the AIR 2014 and they were IR models and theories; IR evaluation, user study and interactive IR; web IR, scalability and IR in social media; multimedia IR; natural language processing for IR; machine learning and data mining for IR and IR applications.
IR Applications -- Leveraging Deletion Neighborhoods and Trie for Efficient String Similarity Search and Join -- Content-based Medical Image Retrieval System for Infections and Fluids in Chest Radiographs -- Topic-focused Summarization of News Events based on Biased Snippet Extraction and Selection -- Query Ambiguity Identification based on User Behavior Information -- IR Evaluation, User Study and Interactive IR -- Revisiting the Evaluation of Diversified Search Evaluation Metrics with User Preferences -- Hybrid Crowd-Machine Methods as Alternatives to Pooling & Expert Judgments -- How Do Sponsored Search Results Affect User Behavior in Web Search? -- Is the First Query the Most Important: An Evaluation of Query Aggregation Schemes in Session Search -- A Comparative Evaluation of 2D and 3D Visual Exploration of Document Search Results -- Multimedia IR -- Multi-resolution Shape-based Image Retrieval using Ridgelet Transform -- Characteristics Classification of Durian Varieties Images for Knowledge Representation by Using Conceptual Graph -- IR Models and Theories -- Integrating Semantic Term Relations into Information Retrieval Systems based on Language Models -- Towards Risk-Aware Resource Selection -- Personalizing Web Search Results based on Subspace Projection -- Aggregating Results from Multiple Related Queries to Improve Web Search over Sessions -- Modified Frequency-based Term Weighting Scheme for Accurate Dark Web Content Classification -- Web IR, Scalability and IR in Social Media -- Online Social Network Profile Linkage -- User Message Model: A New Approach to Scalable User Modeling on Microblog -- Enhanced FastPFOR for Inverted Index Compression -- Natural Language Processing for IR -- Linguistically Enhanced Collocate Words Model -- Named Entity Extraction via Automatic Labeling and Tri-Training: Comparison of Selection Methods -- Contrastive Max-Sum Opinion Summarization -- Extracting Interest Tags from Twitter User Biographies -- Named Entity Recognition in Crime Using Machine Learning Approach -- A New Combination Method based on Adaptive Genetic Algorithm for Medical Image Retrieval -- Leveraging Wikipedia and Context Features for Clinical Event Extraction from Mixed-Language Discharge Summary -- Impact of Stemmer on Arabic Text Retrieval -- Distance Measures and Stemming Impact on Arabic Document Clustering -- Emotional Links between Structure and Content in Online Communications -- Extraction of Semantic Features from Transaction Dialogues -- Extracting Corpus-Specific Strings by Using Suffix Arrays Enhanced with Longest Common Prefix -- Feasibility Study Concerning the Use of Reasoning Technique in Semantic Reasoners -- Machine Learning & Data Mining for IR -- Nature Inspired Data Mining Algorithm for Document Clustering in Information Retrieval -- Enhancing Machine-Learning Methods for Sentiment Classification of Web Data -- Name Disambiguation by Collective Classifcation -- Hierarchical Dirichlet Process Topic Modeling for Large Number of Answer Types Classification in Open Domain Question Answering -- A Comparative Study of Feature Selection and Machine Learning Algorithms for Arabic Sentiment Classification -- Undersampling Techniques to Re-balance Training Data for Large Scale Learning-to-Rank -- Nurturing Filled Pause Detection for Spontaneous Speech Retrieval -- Analysis of Japanese Wikipedia Category for Constructing Wikipedia Ontology and Semantic Similarity Measure -- Correlation-based Feature Selection for Association Rule Mining in Semantic Annotation of Mammographic Medical Images -- Content Quality of Clustered Latent Dirichlet Allocation Short Summaries.
Keywords: Information storage and retrieval; Database management; Application software; Artificial intelligence; Information Storage and Retrieval; Database Management; Information Systems Applications (incl. Internet).; Artificial Intelligence